Uncle Homer's encyclopedia of fishing fish catching tips, tricks, and secrets - Bendell, Leonard; Bieber, Andrew D. ([S.l.] : Penguin Productions, 1988)
Inthis series, Homer Circle brings his vast knowledge of sport and unlocks those mysteries of fishing so that you can have more fun while improving your catch
Editor, Mike Palma ; writer, Homer Circle
Narrator
Keywords: Fishing -- Encyclopedias; Fishing -- Equipment and supplies -- Encyclopedias